Preservice EFL teachers’ talk during a teaching practicum at a lower secondary school: A report on video-stimulated reflection (VSR) - Zulaiha, Siti; Mulyono, Herri (Argentinian Journal of Applied Linguistics - ISSN 2314-3576, 2022)
This article reports on a small scale qualitative investigation into English as a foreign language (EFL) pre-service teachers’ perception of their own talk during a teaching practicum at a lower secondary school in Jakarta, Indonesia. Three preservice EFL teachers participating in the study were asked to videotape their activities during a classroom teaching and write reflections. Content analysis was employed to analyse such reflections with a focus on three aspects of preservice EFL teachers’ talk, including types and function of talk and the amount of talk during classroom instruction. The results of the analysis highlight the sequence initiation-response-feedback (IRF). The results also show the role of beliefs about EFL learning and a good EFL teacher in determining the amount of teacher talk. More importantly, such beliefs have been primary drivers for the teachers to use the target language as a medium of instruction regardless their students’ level of English proficiency.